Defect-engineered surfaces to investigate the formation of self-assembled molecular networks. Issue 44 (2nd November 2022) - Yu, Li-Hua; Cai, Zhen-Feng; Verstraete, Lander; Xia, Yuanzhi; Fang, Yuan; Cuccia, Louis; Ivasenko, Oleksandr; De Feyter, Steven
Abstract : We showcase the use of covalently modified HOPG for the investigation of domain size controlled 2D self-assembly, nucleation and growth kinetics, molecular adsorption/desorption thermodynamics, and tip-induced selective recrystallization. Abstract : Herein we report the impact of covalent modification (grafting), inducing lateral nanoconfinement conditions, on the self-assembly of a quinonoid zwitterion derivative into self-assembled molecular networks at the liquid/solid interface. At low concentrations where the compound does not show self-assembly behaviour on bare highly oriented pyrolytic graphite (HOPG), close-packed self-assembled structures are visualized by scanning tunneling microscopy on covalently modified HOPG. The size of the self-assembled domains decreases with increasing the density of grafted molecules, i.e. the molecules covalently bound to the surface. The dynamics of domains are captured with molecular resolution, revealing not only time-dependent growth and shrinkage processes but also the orientation conversion of assembled domains. Grafted pins play a key role in initiating the formation of on-surface molecular self-assembly and their stabilization, providing an elegant route to study various aspects of nucleation and growth processes of self-assembled molecular networks.